2020
DOI: 10.1016/j.breast.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of standard low-dose anthracycline chemotherapy on late congestive heart failure in breast cancer survivors aged between 50 and 59 at diagnosis: A nationwide study

Abstract: Objectives Although chemotherapy-induced congestive heart failure (CHF) is a well-known adverse event in cancer survivors, the long-term risk of standard low-dose anthracycline has not yet been reported. This study aimed to investigate the long-term effects of standard anthracycline on late CHF in breast cancer survivors. Materials and methods A nationwide retrospective cohort study was conducted using the national insurance claims data for nearly 98% of Korean citizens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Although the benefits of radiotherapy far outweigh the risk of heart diseases, some studies have found increased incidence of and mortality due to heart disease in women subjected to radiotherapy techniques ( Darby et al, 2013 ; Taylor et al, 2017 ). Knowledge on cardiotoxic effects of anthracycline-based chemotherapy regimens have led to lowering of doses and less use of bolus injections to reduce peak concentrations of anthracyclines ( Foukakis et al, 2016 ), but it is estimated that the risk of heart failure associated with anthracyclines remains increased for standard low-dose group as compared to non-users ( Chung et al, 2020 ). While trastuzumab has been shown to reduce the risk of breast cancer mortality at 11 years of follow-up ( Cameron et al, 2017 ), evidence on its cardiotoxicity is conflicting ( Bowles et al, 2012 ; Papakonstantinou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the benefits of radiotherapy far outweigh the risk of heart diseases, some studies have found increased incidence of and mortality due to heart disease in women subjected to radiotherapy techniques ( Darby et al, 2013 ; Taylor et al, 2017 ). Knowledge on cardiotoxic effects of anthracycline-based chemotherapy regimens have led to lowering of doses and less use of bolus injections to reduce peak concentrations of anthracyclines ( Foukakis et al, 2016 ), but it is estimated that the risk of heart failure associated with anthracyclines remains increased for standard low-dose group as compared to non-users ( Chung et al, 2020 ). While trastuzumab has been shown to reduce the risk of breast cancer mortality at 11 years of follow-up ( Cameron et al, 2017 ), evidence on its cardiotoxicity is conflicting ( Bowles et al, 2012 ; Papakonstantinou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging studies emphasized the adverse effects of anthracyclines, and further efforts have been made to prevent and treat them, especially against cardiotoxicity 19–21 . Several drugs and/or therapies are proposed as cardioprotective agents/approaches during the treatment with ABC, such as dexrazoxane, β‐blockers, ACE inhibitors, telomerase therapy, and matrix metalloproteinase inhibitors 22–26 .…”
Section: Discussionmentioning
confidence: 99%
“…Taylor et al, 2017). Knowledge on cardiotoxic effects of anthracycline-based chemotherapy regimens have led to lowering of doses and less use of bolus injections to reduce peak concentrations of anthracyclines (Foukakis et al, 2016), but it is estimated that the risk of heart failure associated with anthracyclines remains increased for standard low-dose group as compared to non-users (Chung et al, 2020).…”
Section: Introductionmentioning
confidence: 99%